Fragmentation of Human Neutrophil α-Defensin 4 to Combat Multidrug Resistant Bacteria - Ehmann, Dirk; Koeninger, Louis; Wendler, Judith; Malek, Nisar P.; Stange, Eduard F.; Wehkamp, Jan; Jensen, Benjamin A. H. (Frontiers in Microbiology, 2020)
The occurrence and spread of multidrug-resistant bacteria is a prominent health concern. To curb this urgent threat, new innovative strategies pursuing novel antimicrobial agents are of the utmost importance. Here, we unleashed the antimicrobial activity of human neutrophil peptide-4 (HNP-4) by tryptic digestion. We identified a single 11 amino acid long fragment (HNP-41-11) with remarkable antimicrobial potential, exceeding that of the full length peptide on both mass and molar levels. Importantly, HNP-41-11 was equally bactericidal against multidrug-resistant and non-resistant strains; a potency that was further enhanced by N- and C-terminus modifications (acetylation and amidation, respectively). These observations, combined with negligible cytotoxicity not exceeding that of the full length peptide, presents proteolytic digestion of innate host-defense-peptides as a novel strategy to overcome the current health crisis related to antibiotic-resistant bacteria.